A Novel False Data Injection Attack Formulation Based on CUR Low-Rank Decomposition Method - Mukherjee D.; Ghosh S.; Misra R.K. (My University, 2025)
State estimation algorithms deployed in modern grids are vulnerable towards false data injection attacks. This work demonstrates a novel attack vector (AV) formulation scheme by exploiting the low-rank subspace of the topology matrix. With constraints over the state deviation vector, this work showcases that the developed AV can effectively bypass the residue test for a demonstrated test bench. © 2010-2012 IEEE.